2014
DOI: 10.1016/j.ijme.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Engaging students in group work to maximise tacit knowledge sharing and use

Abstract: a b s t r a c tWe investigated how students' interpersonal trust relationships impact on their willingness to share knowledge during group work and whether there is one best method of group allocation to maximise knowledge sharing. Through focus groups with 32 undergraduate and postgraduate students, we found: i) participants had limited experience of sharing skills; ii) they were more frequently engaged in sharing their beliefs, values and ideas; iii) while interpersonal relationships impacted upon the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…This was facilitated by the fact that students worked with people they have a good connection with and who are accommodated in places closer to their place of residence. Most students prefer to work with peers who are academically good, even though they are not friends, they chose them because of a fear of losing marks (Analoui, Sambrook & Doloriert, 2014) Smith and Rogers (2014) recommended that nursing programmes should include teaching methodologies that stimulate engagement, which is also part of a team work process in order to build skills required for successful team outcome. For the Namibian BNSc programme, lecturers were encouraged to use group works as teaching strategiesso that students are more prepared for team-based assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This was facilitated by the fact that students worked with people they have a good connection with and who are accommodated in places closer to their place of residence. Most students prefer to work with peers who are academically good, even though they are not friends, they chose them because of a fear of losing marks (Analoui, Sambrook & Doloriert, 2014) Smith and Rogers (2014) recommended that nursing programmes should include teaching methodologies that stimulate engagement, which is also part of a team work process in order to build skills required for successful team outcome. For the Namibian BNSc programme, lecturers were encouraged to use group works as teaching strategiesso that students are more prepared for team-based assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Liking and knowledge sharing: exploring the direct relationship A study by Analoui et al (2014) showed a possible relationship between liking and knowledge sharing in a group work setting. Their study found that participants felt more at ease sharing knowledge if they felt a familiarity with their co-workers (Analoui et al, 2014). Labianca and Brass (2006) found that feelings of dislike hampered the willingness to share information.…”
Section: Trust and Knowledge Sharingmentioning
confidence: 99%
“…While there are multiple debates, which consider the conceptualisation of knowledge, the tacit/explicit distinction is the most practical and common (Pathirage et al 2007), with this particular typology having already been applied within a pedagogic context (Analoui et al 2014). Where students view the purchase of knowledge as a product, they are more than likely holding to a conceptualization of explicit knowledge.…”
Section: Consumerisation In Higher Educationmentioning
confidence: 99%